ANALISIS SISTEM DAN PROSEDUR PENGADAAN KAS DAN PEMBAYARAN DANA PENSIUN PADA PT. POS INDONESIA CABANG MANADO - Putri, Gracia Miranda; Nangoi, Grace; Alexander, Stanly (Universitas Sam Ratulangi, 2018)
Pension Funds play a very important role in the development of both economic and social welfare. The Pension Fund is a legal entity that manages and operates a program that promises retirement benefits. Implementation of cash procurement and pension fund payment at PT. Pos Indonesia Branch Manado can be done easily and does not take a long time because it uses a good system and procedures, and can illustrate how the implementation of internal controls on the procurement of cash and pension payments. The research method used in this thesis research is descriptive method whose purpose every data collected is analyzed and then drawn a conclusion and research type used is qualitative descriptive. The results obtained that the system and procedures of cash procurement and payment of pension funds at PT. Pos Indonesia Branch Manado runs well, in accordance with established standards, and is supported by the Fund Distribution system. Implementation of internal controls on the system and procedures of cash procurement and payment of pension funds at PT. Pos Indonesia Branch Manado has been run well because it is implemented in accordance with standard operating policy guidelines procedures and policies of directors.Keywords: System and Procedure, Cash Procurement, Pension Fund Payment.